Low-Level Languages and Packages in Artificial Intelligence Markup Language - Sisodia, Shailendra Singh; Singh, Vineet (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 8 No 1 (2024): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2024)
This article explores the intricacies of low-level programming languages, delving into their direct hardware control, while also investigating Artificial Intelligence Markup Language (AIML) packages that leverage XML-based patterns for abstracting natural language processing in artificial intelligence. The study aims to bridge the gap between hardware-level optimisation and high-level natural language understanding through an in-depth analysis of low-level languages and AIML packages.